Fashion, art and society: The pioneering maison Canada-de-Luxe and the emergence of the national fashion industry in the 1950s (ModaPalavra e-periódico, 2014)
Today, Brazilian fashion has prominence and international recognition for its distinctive style to create clothing and launch trends, a movement that seeks to unite the unique cultural diversity of Brazil to what is more contemporary and global in fashion design worldwide. However, the fashion system in Brazil has a history and its starting point goes back to the 1950s, furthermore, it was part of a large gear which articulated various industries and social sectors inside and outside the field of fashion. It is within this great gear that we can position the Canadá-de-Luxe and the creations of Mena Fiala – who never set out to create a fashionable Brazilian vanguard, but was relentless in the consolidation of a fashion tuned with was being produced outside Brazil, especially in Paris Post War fashion. Armed with an elaborate technique that she herself invented, never stopped developing it without abandoning the canons that constitute the style in fashion: effort, persistence and beauty. The house Canada’s benchmark comes to fashion in Brazil in the 1950s due to the tireless efforts of Mena Fiala and Cândida Gluzman in transforming the brand Canadá in reference of beauty and elegance.